THE SUBTLETIES OF TABLE TOASTS IN RUSSIAN AND CHINESE LANGUAGES (Philological Studies, 2019)
The article is devoted to the subtleties of Chinese and Russian table etiquette. Table toast is an important part of the table culture. The author of the article considers the using of table toasts in Russian and Chinese languages. The linguistic form of toasts is an important object of research, which allows to show the differences between Chinese and Russian cultures. The article reveals the content of such concepts as “wish” and “congratulation”, and also describes the features of their implementation in speech acts. Table toasts in each of these two languages are characterized by stylistic heterogeneity and include typical stereotypes of the national culture of Russia and China.
Keywords: table toast, etiquette, congratulation, greeting, comparative studies